(untitled) (American Journal of Aquaculture and Animal Science, 2025)
This study aimed to assess the diversity and abundance of mammal species in the Somali Regional state of Ethiopia, identify key threats, and document habitat preferences and distribution patterns. Three agro-ecological zones (Tepid to Cool Moist Plain, Hot Arid Lowland, and Warm Moist Lowland), covering approximately 83.95% (31.47 million ha) of the region, were purposively selected. Within each zone, three woredas were chosen, and in each woreda, three distinct habitat patches were identified based on vegetation structure and topography, yielding a total of 27 study sites. A descriptive research design was employed, utilizing key informant interviews (KIIs) and focus group discussions (FGDs). Findings indicate a declining trend in wild mammal populations, particularly antelope species such as the Lesser Kudu and Oryx, as well as carnivores like lions. Major threats include human settlement expansion, habitat degradation, recurrent droughts, and illegal hunting. The study recommends expanding protected areas, restoring habitats, and establishing community-based conservation initiatives. Emphasis is placed on integrating traditional ecological knowledge and promoting sustainable land-use practices. It also highlights the need for continued research, capacity building, education, and the development of supportive policies and legal frameworks for wildlife conservation.